Compressive Strength and Density of Oil Palm Shell Lightweight Aggregate Concrete Containing Palm Oil Fuel Ash under Different Curing Regime - Khairunisa, Muthusamy; Nur Azzimah, Zamri; Norhaiza, Ghazali; Sharifah Maszura, Syed Mohsin (2015)
Efforts to reduce quantity of oil palm shell and palm oil fuel ash from being disposed as environmental polluting waste has result in innovation of oil palm shell lightweight aggregate concrete containing palm oil fuel ash as partial cement replacement. The current investigation looks into the effect of curing methods on density and compressive strength performance of this newly modified lightweight concrete. Plain concrete consist of 100% OPC were used as control specimen and another one is produced by integrating 20% ground palm oil fuel ash by weight of cement. The specimens were produced in form of cubes (100mmx100mmx100mm) and subjected to different curing method up to 60 days. Four types of curing method were applied namely continuous water curing, sprayed curing, air curing and natural weather curing. Compressive strength test were conducted in accordance to BS EN 12390-3 at 7, 28 and 60 days. The results reveal that strength development of oil palm shell lightweight aggregate containing palm oil fuel ash depends on the frequency of water supplied during curing age. Continuous water curing is the most suitable type of curing as it promotes better hydration process and pozzolanic reaction in the concrete mix. Formation of larger amount of C-S-H gel makes the concrete internal structure denser and able to sustain larger load compared to plain concrete.